Microfiber optomechanical torsion sensor - Zhang, Qiang; Zhang, Jie; Yang, Shiwei; Zhai, Ruili; Xie, Yuyang; Li, Yongmin (Frontiers in Physics, 2023)
In this paper, we propose and demonstrate experimentally an optomechanical torsion sensor using a microfiber mechanical resonator. The torsion angle could be obtained by monitoring the resonant frequency shifts of the microfiber resonator. Theoretical and experimental results show that the shift of resonant frequency is nonlinear to the torsion angle, and the fundamental mode is more sensitive than other higher modes. The highest sensitivity of the sensor tested in our experiments is 1687 Hz/degree, and the corresponding resolution of torsion angle is up to 0.0006 degree, which is 2 orders of magnitude higher than that of the reported fiber-optic torsion sensors. The proposed sensor is a promising candidate for the practical engineering applications.